2020
DOI: 10.13106/jafeb.2020.vol7.no10.377
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Salesperson’s Personality to Job Performance in Machinery Industry in Viet Nam

Abstract: This research focuses on identifying and measuring key personality factors affecting the job performance of salesperson working in the machinery industry in Vietnam. A total number of 218 salesperson working in machinery industry were surveyed. After evaluating Cronbach's Alpha and using the regression analysis technique, the results show the impact level of personality trait factors affecting the job performance of salesperson working in machinery industry. Ordered from the highest to the lowest effects on jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…Employees with openness-to-experience personality trait are also likely to exhibit high levels of service performance due to their autonomy, intellectual curiosity, adaptability and need for variety (Bing and Lounsbury, 2000; Costa and McCrae, 1992). Our results align with previous studies by Huynh et al (2020) and Shahreki et al (2020) regarding the positive association between extraversion and employee service performance. However, our study distinguishes itself from these works by delving into employee service performance as a performance outcome of extraversion personality, whereas prior studies have examined the predictive role of extraversion on job performance in general.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Employees with openness-to-experience personality trait are also likely to exhibit high levels of service performance due to their autonomy, intellectual curiosity, adaptability and need for variety (Bing and Lounsbury, 2000; Costa and McCrae, 1992). Our results align with previous studies by Huynh et al (2020) and Shahreki et al (2020) regarding the positive association between extraversion and employee service performance. However, our study distinguishes itself from these works by delving into employee service performance as a performance outcome of extraversion personality, whereas prior studies have examined the predictive role of extraversion on job performance in general.…”
Section: Discussionsupporting
confidence: 93%
“…However, our study distinguishes itself from these works by delving into employee service performance as a performance outcome of extraversion personality, whereas prior studies have examined the predictive role of extraversion on job performance in general. Furthermore, our finding regarding the positive link between openness to experience and employee service performance is consistent with the findings from Frieder et al (2018) and Huynh et al (2020). However, while our study focuses on employee service performance stimulated by openness to experience, those studies unpacked job performance in general as the performance outcome of open-to-experience personality.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…performance and satisfaction, career success, and life quality (Barrick & Mount, 1991;Fullarton et al, 2013;Hagberg, Hagberg, & Saveman, 2002;Han, 2020;Huynh et al, 2020;Jalal et al, 2019;Nettle, 2007;Sutin et al, 2009;Wrosch & Scheier, 2003). Nettle (2007) suggested that personality -"what makes you the way you are" -is described as a personal disposition that can predict what they will do.…”
mentioning
confidence: 99%
“…Moreover, research has indicated that stress is a noteworthy factor in predicting low job satisfaction (Yang et al, 2021). Based on the above evidence, it could be speculated that gratitude, stress, and job satisfaction are closely related.…”
Section: Backg Rou N Dmentioning
confidence: 95%